2003
DOI: 10.1002/ar.b.10024
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D analysis of the canal network in cortical bone by micro‐computed tomography

Abstract: Cortical bone is perforated by an interconnected network of porous canals that facilitate the distribution of neurovascular structures throughout the cortex. This network is an integral component of cortical microstructure and, therefore, undergoes continual change throughout life as the cortex is remodeled. To date, the investigation of cortical microstructure, including the canal network, has largely been limited to the two-dimensional (2D) realm due to methodological hurdles. Thanks to continuing improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 61 publications
4
155
0
3
Order By: Relevance
“…Considering their mean diameter of 158 µm, the micro-channels could contain both small arterioles and venules, which have diameters around 30 µm and 10 to 60 µm, respectively (Boulpaep, 2009). Haversian canals are well known in bone providing a vascular supply for the tissue, but these canals are smaller up to 45 µm in diameter and usually only containing capillaries (Cooper et al, 2003); thus, such canals were below the resolution of our method (40-60 µm).…”
Section: Discussionmentioning
confidence: 82%
“…Considering their mean diameter of 158 µm, the micro-channels could contain both small arterioles and venules, which have diameters around 30 µm and 10 to 60 µm, respectively (Boulpaep, 2009). Haversian canals are well known in bone providing a vascular supply for the tissue, but these canals are smaller up to 45 µm in diameter and usually only containing capillaries (Cooper et al, 2003); thus, such canals were below the resolution of our method (40-60 µm).…”
Section: Discussionmentioning
confidence: 82%
“…On the basis of synchrotron radiation mCT images of cortical bone, Schneider et al 74 reported mouse strain and sex-related differences in vascular channel structure and density. In human bone, Cooper et al 75 , using skeletonization techniques were able to image and quantify the density and connectivity of the cortical 'vascular' porosity. Their work suggests that threedimensional morphologic analysis of the canal network may provide novel insights into bone physiology that are not possible with two-dimensional approaches.…”
Section: Bone Vascularization M-h Lafage-proust Et Almentioning
confidence: 99%
“…The application of different methods of study based on histology [5,9,18,30,31] or micro-CT [6,7] has led to several three-dimensional models of the canal network. These reconstructions can be useful to give a general view of the architecture of the system but are limited by the loss of morphologic details and the sense of temporal development.…”
Section: Introductionmentioning
confidence: 99%